Estado nutricional durante la gestación y su relación con hábitos alimenticios en pacientes atendidas en el Hospital II -1 Moyobamba septiembre 2015 – enero 2016 - Catip Tawan, Renoir (2016)
This study entitled "Nutritional status during pregnancy and their relationship with eating habits in patients treated at the Hospital II-1 Moyobamba. September 2015 - January 2016 no experimental, quantitative, descriptive, cross with prospective data collection retro Study. Whose sample was 156 pregnant women who were administered a survey conducted by the authors. Results: The predominant Socio-demographic characteristics of pregnant women were: 61.5% (96) are pregnant housewife, 64.1% profess the Catholic religion (100), 84.6% (132 ) come from urban areas and 62.2% (94) have rented or borrowed housing. 61.5% (96) range from 20 to 35 years and have a grade of incomplete secondary education (55.8%). average pregnant attended size is 1.52 meters and the average weight is 55.87 kg. 60.3% (94) is located a body mass index 18.5 to 24.9 (normal weight), as eating habits: 48.0% (74), are unsuited habits, 46.0% (72) they have good habits and 6.0% (10) inadequate eating habits. In conclusion: In applying the non-parametric statistical tests chi-square (x ^ 2) found that if there is a statistically significant relationship between dietary habits and nutritional status of the served pregnant at the Hospital II-1 Moyobamba, (X2 = 15,015; p <0.05).